الإستراتيجيات الحديثة لتعليم التربية الديتية في ضوء الأحاديث النبوية = Modern strategies for teaching Islamic education in the light of the prophet's hadith - Said, Mohamed Mohamed Tolba; Abd Rashid, Adnan (Institut Kajian Hadis (INHAD), Kolej Universiti Islam Antarabangsa Selangor (KUIS), 2018)
This research aims to study "Modern Strategies For Teaching Islamic Education In The Light Of The Prophet's Hadith". The importance of this topic is that the Prophet Muhammad is the Role model and good example of the teachers throughout the eras of Human being and His Hadiths include modern strategies for teaching Islamic education to the generations of the Islamic nations, to build a global culture and developing communication between Arabic Islamic culture and other cultures. The objectives of the research were to highlight the modern strategies in teaching of "Islamic education", including: the strategy of brain-storming - the latest educational strategies - the strategy of feedback and evaluation, Mental maps and explanatory symbols, Problem–Solving strategy, case study strategy, and other modern educational strategies. The methodology used in this research is the descriptive approach to analyze the data obtained and critique it to draw conclusions. The results of this research are The noble Prophet's Hadith had included all the modern strategies for teaching "Islamic education" in the twenty first century, and the researchers and teachers in the field of education should to follow the teaching methods of the Prophet Muhammad peace be upon him in teaching because he is the teacher of mankind.